English Language Teaching (ELT): Guidance Learning For Primary School Students on Sajoanging, Wajo Regency - Satriani; Bahri, Syamsul; Muzkiyah, Nurul; Putriani, Nur (Jurnal Pengabdian Kepada Masyarakat Patikala, 2022)
The PKM tutoring program's objective is to provide English tutoring to elementary school students as a way to develop their English communication skills. It is especially for students to get an understanding of fundamental English material and to be able to speak basic English words and sentences in everyday situations. The PKM guidance is located in Wajo Regency's Sojoanging sub-district. The socialization, training, and supervision methods are used to implement community service for English language tutoring for elementary school students. Playing, singing, spelling, pronouncing, and role-playing are some of the strategies used to guide and train children. The results of PKM of elementary school students before tutoring revealed that the children had difficulties pronouncing English words at the start of the English tutoring session. Even while some participants continued to say the words incorrectly after the third meeting, the students had begun to pronounce the words correctly. Furthermore, the learning outcomes of elementary students before tutoring revealed that just one child out of twenty graduated. Following the English coaching, the exam results revealed that all 20 primary school students who took the test passed with an average score of 75.